Intraplate Magmatism and Metallogeny of North Vietnam - Tran, Hoa Trong; Polyakov, Gleb V.; Tran, Anh Tuan; Borisenko, Alexander S.; Izokh, Andrey E.; Balykin, Pavel A.; Ngo, Phuong Thi; Pham, Dung Thi (Modern Approaches in Solid Earth Sciences,, 2016)
This book by Vietnamese and Russian authors is the first of its kind and combines the extensive knowledge on the petrology and metallogeny of the late Paleozoic - early Mesozoic and Cenozoic periods in North Vietnam. The Permian - Triassic and Paleogene volcano-plutonic and plutonic associations are two important geological events in the evolutionary history of Southeast Asia, including the 260 - 250 Ma Emeishan mantle plume and Indian-Eurasia collision at 60 - 55 M. The volume includes 9 chapters,  divided into 3 parts. Part 1 introduces the geological structure of North Vietnam; Part 2 covers the Permian - Triassic magma associations and metallogeny; and Part 3 focuses on  the Cenozoic magma associations and metallogeny. In each chapter, the geological setting of magmas, classification of different geological structures, and  composition characteristics, such as mineralogy, geochemistry, isotope systematics and geochronology are discussed.  This  book represents an important reference document for international and Vietnamese geologists engaged in the geological  history and metallogeny of Vietnam, an important area  of the Asian continent. The monograph also has a practical significance in contributing new premises and  to assess rare and precious mineral prospects. In addition, it can be regarded as a necessary data base for petrological and metallogenic projects and university courses.  .